Putting Proteomics Into Immunotherapy for Glioblastoma - Chen, Liangyu; Qin, Di; Guo, Xinyu; Wang, Qixue; Li, Jie (Frontiers in Immunology, 2021)
In glioblastoma, the most aggressive brain cancer, a complex microenvironment, heterogeneity and immunechaos, are considerable hurdles to classify the subtypes and promote treatment progression. The standard therapies for many other cancers do not effectively prolong the survival of patients due to the unique location and heterogeneous characteristics of glioblastoma. Immunotherapy has shown a promising effect for many other tumors, but its application for glioma still has some challenges. The recent breakthrough of high-throughput LC-MS/MS systems has allowed researchers to update their strategy for identifying and quantifying thousands of proteins in a much shorter time with less effort. The protein maps can contribute to generating a complete map of regulatory systems to elucidate tumor mechanisms. In particular, newly developed unicellular proteomics could be used to determine the microenvironment and heterogeneity. In addition, the large scale of differentiated proteins provides more ways to precisely classify tumor subtypes and construct a larger library for biomarkers and biotargets, especially for immunotherapy. Thus, the combination of proteomics and immunotherapy may accelerate research on the treatment of glioblastoma. In this review, we evaluate the frontline applications of proteomics strategies for immunotherapy and related mechanisms in glioblastoma research.